What is the answer to this problem
2 answers:
X=0 is the answer.
6(x + -3) + 10 = 2(3x + -4)
<span>Reorder the terms:
6(-3 + x) + 10 = 2(3x + -4)
(-3 * 6 + x * 6) + 10 = 2(3x + -4)
(-18 + 6x) + 10 = 2(3x + -4)
Reorder the terms:
-18 + 10 + 6x = 2(3x + -4)
Combine like terms: -18 + 10 = -8
-8 + 6x = 2(3x + -4)
Reorder the terms:
-8 + 6x = 2(-4 + 3x)
-8 + 6x = (-4 * 2 + 3x * 2)
-8 + 6x = (-8 + 6x)
Add '8' to each side of the equation.
-8 + 8 + 6x = -8 + 8 + 6x
Combine like terms: -8 + 8 = 0
0 + 6x = -8 + 8 + 6x
6x = -8 + 8 + 6x
Combine like terms: -8 + 8 = 0
6x = 0 + 6x
6x = 6x
Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x
Combine like terms: 6x + -6x = 0
0 = 6x + -6x
Combine like terms: 6x + -6x = 0
0 = 0</span>
To your problem the answer is
x=0
You might be interested in
Milk carton
Perfume bottle
Answer:
Tehhehheeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeeee
Step-by-step explanation:
Answer:
Hope it helps plz give BRAINLIES! :D
Step-by-step explanation:
$80